2018
DOI: 10.1051/matecconf/201819002004
|View full text |Cite
|
Sign up to set email alerts
|

Incremental magnetic pulse welding of dissimilar sheet metals

Abstract: Magnetic pulse welding is a solid state welding process using pulsed magnetic fields resulting from a sudden discharge of a capacitor battery through a tool coil in order to cause a high-speed collision of two metallic components, thus producing an impact-welded joint. The joint is formed at room temperature. Consequently, temperature-induced problems are avoided and this technology enables the use of material combinations, which are usually considered to be non-weldable. The extension of the typically linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…It was demonstrated that these parameters must be adjusted, depending on the properties of the applied materials. For example, Psyk et al [ 4 ] presented the results of joining copper alloys with aluminum alloys. Shanthala et al [ 5 ] optimized the MPW process for joining two steel parts.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that these parameters must be adjusted, depending on the properties of the applied materials. For example, Psyk et al [ 4 ] presented the results of joining copper alloys with aluminum alloys. Shanthala et al [ 5 ] optimized the MPW process for joining two steel parts.…”
Section: Introductionmentioning
confidence: 99%